Population structure of a widespread bat (Tadarida brasiliensis) in an island system. Issue 19 (17th August 2017) - Speer, Kelly A.; Petronio, Brandi Jo; Simmons, Nancy B.; Richey, Rebecca; Magrini, Kristin; Soto‐Centeno, J. Angel; Reed, David L.
Abstract: Dispersal is a driving factor in the creation and maintenance of biodiversity, yet little is known about the effects of habitat variation and geography on dispersal and population connectivity in most mammalian groups. Bats of the family Molossidae are fast‐flying mammals thought to have potentially high dispersal ability, and recent studies have indicated gene flow across hundreds of kilometers in continental North American populations of the Brazilian free‐tailed bat, Tadarida brasiliensis . We examined the population genetics, phylogeography, and morphology of this species in Florida and across islands of The Bahamas, which are part of an island archipelago in the West Indies. Previous studies indicate that bats in the family Phyllostomidae, which are possibly less mobile than members of the family Molossidae, exhibit population structuring across The Bahamas. We hypothesized that T. brasiliensis would show high population connectivity throughout the islands and that T. brasiliensis would show higher connectivity than two species of phyllostomid bats that have been previously examined in The Bahamas. Contrary to our predictions, T. brasiliensis shows high population structure between two groups of islands in The Bahamas, similar to the structure exhibited by one species of phyllostomid bat. Phylogenetic and morphological analyses suggest that this structure may be the result of ancient divergence between two populations of T. brasiliensis that subsequently came into contact in The Bahamas. Our findings additionally suggest that there may be cryptic species within T. brasiliensis in The Bahamas and the West Indies more broadly. Abstract : We examined the population genetics, phylogeography, and morphology of a highly mobile bat in Florida and across islands of The Bahamas. This bat exhibited strong differentiation in The Bahamas across all data types, similar to the differentiation exhibited by less‐mobile species of bat. Phylogenetic and morphological analyses suggest that two populations diverged in the past and subsequently came into contact in The Bahamas and that one of these populations may represent a cryptic species.